Ameliorative effects of betanin in mice with trimethyltin-induced pancreatic and hepatocytic alterations - Wachiryah Thong-Asa,; Yanisa Detpakdee,; Kanlayawadee Srisoonthon, (Penerbit Universiti Kebangsaan Malaysia, 2025)
The effects of TMT on metabolic alteration are on the rise, including obesity and diabetes. In the present study, we aimed to investigate the protective effect of betanin (Bet) against TMT-induced glycemic disturbance and pancreatic and hepatocytic alterations, expanding on TMT’s and Bet’s effects on metabolic diseases. Fifty male Institute of Cancer Research (ICR) mice were randomly divided into Sham-veh, TMT-L-veh, TMT-H-veh, TMT-L-Bet100, and TMT-H-Bet100 groups. A low dose (L) (1 mg/kg) and high dose (H) (2.6 mg/kg) of TMT were given via one-time intraperitoneal (i.p.) injection before intragastric gavage administration of treatments for 4 consecutive weeks. A weekly oral glucose tolerance test (OGTT) was conducted for glycemic control capacity evaluation with serum insulin assessment. Pancreatic and hepatic tissues were collected to analyze islet number and beta cell density, glycogen content, and histopathology. TMT exposure did not significantly change glycemic control capacity or serum insulin level (p > 0.05). TMT significantly reduced pancreatic beta cell density, and this was accompanied by a decrease in hepatic glycogen content and an increase in hepatosteatosis and inflammation (p < 0.05). Treatment with Bet significantly alleviated all these alterations (p < 0.05). Bet showed alleviative effects against TMT-induced pancreatic and hepatocytic alterations, including preventing pancreatic beta cell damage, maintaining the liver’s glycogen content, anti-hepatosteatosis, and anti-inflammation.